DEVELOPMENT OF LABRASOL®-BASED SNEDDS FOR ENHANCED DELIVERY OF COMBINATION PROPOLIS, SEA CUCUMBER, AND CENTELLA ASIATICAEXTRACTS - Fitriani, Hannie; Syukri, Yandi; Taher, Muhammad (Jurnal Farmasi Sains dan Praktis, 2025)
The therapeutic efficacy of natural extracts such as propolis, sea cucumber or gamat (Stichopus hermanii), and pegagan (Centella asiatica) is supported by their anti-inflammatory, antioxidant, and regenerative properties. However, their pharmaceutical application is limited due to poor solubility and low bioavailability. This study aimed to develop and characterize a Self-Nanoemulsifying Drug Delivery System (SNEDDS) using Labrasol to enhance the delivery and stability of a combination of these three extracts, that exhibit synergistic effects as tissue regeneration, antimicrobial, anti-inflammatory, and antioxidant properties. SNEDDS formulations were prepared by a high energy method with Labrasol, Tween 80, and propylene glycol. The formulations were evaluated for droplet size, polydispersity index (PDI), zeta potential, and thermodynamic stability test. The optimized SNEDDS exhibited nano-sized droplets (151.13 nm ± 17.26) with low PDI (0.39 ± 0.01) and zeta potential (-50.30 ± 1.04) within the stable range, indicating a uniform, physically stable nanoemulsion, and passed the thermodynamic stability test. In conclusion, the optimized SNEDDS formulation demonstrated nano-sized droplets with low PDI and stable zeta potential, indicating good physical stability.